A pilot study of the immunological profile and efficacy of rituximab in muscle-specific kinase antibody-positive myasthenia gravis - Li, Fengzhan; Zhang, Zhouao; Ma, Tianyu; Li, Yuting; Su, Luyao; Wang, Zhouyi; Luo, Tiancheng; Peng, Deyou; Guo, Xinyan; Yang, Mingjin; Du, Xue; Huang, Xiaoyu; et al. (Frontiers in Immunology, 2025)
PurposeThis study summarized the clinical and immunological characteristics of patients with muscle-specific kinase (MuSK) antibody-positive myasthenia gravis (MG), compared their difference with acetylcholine receptor (AChR) antibody-positive MG, and evaluated the therapeutic efficacy of rituximab (RTX) in MuSK-MG.MethodsThis study included 10 MuSK-MG patients and 10 new-onset AChR-MG patients. Clinical and immunological data were collected from medical records before RTX treatment. The efficacy of RTX in MuSK-MG was evaluated by MG-specific activities of daily living (MG-ADL) and quantitative MG (QMG) scores.ResultsAll 10 MuSK-MG patients were female with a mean onset age of 44.3 ± 12.0 years, predominantly presenting with bulbar muscle weakness (90%) and limb weakness (80%). Compared to AChR-MG, MuSK-MG showed higher MG-ADL and QMG scores (P < 0.05), along with more frequent bulbar involvement at disease onset (P = 0.036). Immunological analyses revealed elevated CD19+B cells and memory B cells in MuSK-MG (P < 0.05). CD4+T cells and CD19+B cells showed positive correlations with QMG score (r = 0.766, P = 0.027; r = 0.767, P = 0.026), while natural killer (NK) cells were negatively correlated (r = -0.803, P = 0.005) in MuSK-MG. MuSK-MG patients had a mean MG-ADL score of 8.7 ± 2.5 at baseline. Following RTX treatment, MG-ADL score showed significant improvement, decreasing by -5.1 (95% CI: -7.6 to -2.6) at month 1 and -8.0 (95% CI: -11.0 to -5.0) at month 24. Nine patients took prednisone before RTX, with a median daily dosage of 40.0 mg, which decreased to 2.5 mg/day at month 6, and 8 of 9 (88.7%) patients discontinuing prednisone since month 12.ConclusionMuSK-MG showed distinct clinical and immunological features, including predominant bulbar/limb onset, elevated CD19+B and memory B cells, and disease severity associated CD4+T, CD19+B and NK-cell alterations. In patients with MuSK-MG, low-dose RTX may be associated with long-term and sustained clinical improvement.